Polymorphism of Ag29(BDT)12(TPP)43− cluster: interactions of secondary ligands and their effect on solid state luminescence. Issue 21 (23rd May 2018) - Nag, Abhijit; Chakraborty, Papri; Bodiuzzaman, Mohammad; Ahuja, Tripti; Antharjanam, Sudhadevi; Pradeep, Thalappil
Abstract : We present the first example of polymorphism (cubic & trigonal) in single crystals of an atomically precise monolayer protected cluster, Ag29 (BDT)12 (TPP)4 3− . Abstract : We present the first example of polymorphism (cubic & trigonal) in single crystals of an atomically precise monolayer protected cluster, Ag29 (BDT)12 (TPP)4 3− . We demonstrate that C–H⋯π interactions of the secondary ligands (TPP) are dominant in a cubic lattice compared to a trigonal lattice, resulting in a greater rigidity of the structure, which in turn, results in a higher luminescence efficiency in it.